2007
DOI: 10.1088/0953-8984/19/38/382202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between effects of electric current and magnetic field on transport properties of electron-doped manganite La0.7Ce0.3MnO3thin films

Abstract: We report the effect of electric current and magnetic field, separately and in conjugation, on the transport behaviour of patterned La0.7Ce0.3MnO3 thin films. In the absence of a magnetic field, a significant reduction in peak resistance (Rp) was found with increasing bias current. This effect is also present when a magnetic field is applied, though the magnitude of the electroresistance (ER = [R(I = 0.05 µA)−R(I = 50 µA)]/R(I = 50 µA)) decreases. The metal–insulator transition temperature (Tp) increases both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Wu et al [30] reported a large electroresistance in LCMO thin film with PbZr 0.2 Ti 0.8 O 3 -ferroelectric gate, in a field effect configuration, and they concluded that electroresistance (ER) and CMR effects are complimentary in nature. Similar effects were found in some other thin films [31,32]. The possibility to control the magnetoresistance of ferromagnetic La 0.775 Sr 0.225 MnO 3 (LSMO) thin films on Ba 0.996 Y 0.004 TiO 3 and BaTi 0.85 Sn 0.15 O 3 substrates by electric field was also demonstrated [33].…”
Section: Introductionsupporting
confidence: 70%
“…Wu et al [30] reported a large electroresistance in LCMO thin film with PbZr 0.2 Ti 0.8 O 3 -ferroelectric gate, in a field effect configuration, and they concluded that electroresistance (ER) and CMR effects are complimentary in nature. Similar effects were found in some other thin films [31,32]. The possibility to control the magnetoresistance of ferromagnetic La 0.775 Sr 0.225 MnO 3 (LSMO) thin films on Ba 0.996 Y 0.004 TiO 3 and BaTi 0.85 Sn 0.15 O 3 substrates by electric field was also demonstrated [33].…”
Section: Introductionsupporting
confidence: 70%
“…where coefficients A and B are temperature-dependent parameters containing the information of magneto-elastic coupling of the free energy [43] and electron-electron interaction [44]. For the condition of equilibrium, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The ever-increasing demand of miniaturization in magnetic recording media, with advances in thin film synthesis techniques, has accelerated the investigation of thin films of different materials (Venimadhav et al, 2004;Venimadhav et al, 2005;Ghimpu et al, 2013;Chaudhary, 2015a, 2015b). The applications of thin films are countless as they are now involved in almost every aspect of the physical world (Bajaj et al, 2007a(Bajaj et al, , 2007bSingh et al, 2007;Kumar et al, 2008;Sofin et al, 2011;Raju et al, 2013;Rana et al, 2013;Kamerbeek et al, 2014;Low et al, 2014;Husain et al, 2017). From the household mirror to a computer memory or a solar cell, thin films are widely used for their multiple advantages in different ways.…”
Section: Introductionmentioning
confidence: 99%